50 years of estuarine cockles (Cerastoderma edule L.): Shifting cohorts, dwindling sizes and the impact of improved wastewater treatment. (5th June 2022) - Callaway, Ruth
Abstract: Bivalve populations are prone to change due to sudden or gradual alteration in the natural environment and anthropogenic interference. Fisheries and environmental managers are therefore interested in long-term trends and disentangling natural and human influences, assisting them in conservation efforts and the management of bivalve stocks. Here, 64 monitoring reports covering a 50-year period from 1958 to 2009 of cockles Cerastoderma edule (Linnaeus, 1758) in South Wales, UK, were scrutinised for data on recruitment, growth and mortality. Changes in these population parameters were related to the modernisation of wastewater treatment in 1997, weather and climate variables (temperature, sun hours, air frost days, NAO) and numbers of cockles in the estuary. Recruitment as well as mortalities were high during the first and last decade of the study, and variation was significantly linked to the total number of cockles in the population. Cockle sizes of all cohorts as well as overall biomass declined in the late 1990s. Modernisation of wastewater treatment was significantly related with the downward trend, suggesting that the changed nutrient regime in the estuary may have resulted in reduced food provision for cockles. The average size of newly settled cockles was related to their mortality: the smaller the recruits the higher their mortality. The study indicated a link between the change in wastewater treatment in 1997 and diminishing sizes of cockle recruits that shortened their life span. Survey methods were profoundly changed after 2009, and it is recommended to develop conversion factors between the pre- and post-2009 survey methods. This would allow an extension of the timeline and deeper insight into the long-term impact of the change in wastewater treatment and the recovery of the cockle population. Graphical abstract: Image 1 Highlights: Estuarine bivalve populations experience dramatic inter-annual variation in recruitment success, growth, cohort structure and mortalities. The cockle Cerastoderma edule undergoes distinct decadal phases of high recruitment and mortalities. Size and biomass declined after the modernisation of wastewater treatment works. Small-sized cockle recruits could be linked to higher mortalities.